دور عمليات التحسين المستمر في تحقيق إدارة الجودة الشاملة في المؤسسة الاقتصادية -دراسة حالة مؤسسة كوندور برج بوعريريج- - عامر, حبيبة; فرحات, عباس (جامعة الوادي - University of Eloued, 2017)
This study aims at identifying the role of continuous improvement processes in the achievement of TQM in one of the Algerian institutions, the "CONDOR" organization. To achieve the objective of the study, 37 questionnaire forms were obtained from a total of (40) questionnaires distributed, Assumptions Using the statistical package for social sciences, the study reached several results, the most important of which is the existence of a statistically significant relationship between continuous improvement processes and the principles of TQM (customer focus, continuous improvement, management leadership, employee participation, Decent, training and education).
The role of continuous improvement processes in the achievement of TQM in the economic institution - Case study of the Condor Bordj Bou Arreridj
مقال
Keywords: التحسين المستمر؛ الجودة، إدارة الجودة؛ إدارة الجودة الشاملة.